Mechanisms of heavy metal immobilization and transformation during co-pyrolysis of pig manure with typical organic solid wastes - Fengxiao Zhao; Danni Li; Hongyuan Chen; Xianhai Zeng; Rui Shan; Lu Lin; Haoran Yuan; Yong Chen (Journal of Hazardous Materials, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Photo-crosslinkable quaternized chitosan-based hydrogel for immunomodulation and functional recovery in spinal cord injury - Kaixuan Chen; Min Lin; Danni Zhou; Kailei Xu; Jin Mei; Chunyu Chang; Mengxiang Zhu; Chenhui Zhou (Carbohydrate Polymers, 2026)

A Novel Long-range Excitatory Neural Circuit from the Magnocellular Red Nucleus to Spinal Dorsal Horn Facilitates Neuropathic Pain-like Behaviors in Male Mice - Jiali Shi; Yinfeng Yuan; Yuhao Luo; Yue Guo; Jiashu Lian; Lin Lin; Danni Chen; Qian Wang; Xiumin Xue; Zhichao Chen; Yongjie Wang; Zhihui Huang (Neuroscience Bulletin, 2026)
Neuropathic pain arises from a primary lesion or disease affecting the somatosensory system; however, the brain circuitry underlying the regulation of neuropathic pain remains unclear. The red nucleus (RN) is a critical brain region involved in regulating muscle tension, coordinating movement, and facilitating sensorimotor integration. While some evidence has shown that RN regulates pain, its specific role in neuropathic pain and associated neural circuits remains elusive. In this study, we found that CaMKIIα-positive neurons in the magnocellular red nucleus (RMC CaMKIIα ) were activated following common peroneal nerve (CPN) ligation-induced chronic neuropathic pain in adult male mice. Interestingly, chemogenetic and optogenetic inhibition of these RMC CaMKIIα neurons alleviated the thermal hyperalgesia and mechanical allodynia in the neuropathic pain model mice, whereas activation of these neurons sufficiently induced the mechanical allodynia and thermal hyperalgesia in naïve mice. Trans-synaptic viral tracing studies further revealed that long-range CaMKIIα + neuron projections from RMC to the dorsal horn (DH) facilitated the neuropathic pain-like behaviors following CPN ligation. DH neurons received direct innervation from RMC CaMKIIα neurons, and inhibition of RMC CaMKIIα -DH CaMKIIα circuits alleviated the neuropathic pain in the ligated mice. Taken together, these results identify a novel long-range excitatory neural circuit from RMC to DH that facilitates the neuropathic pain-like behaviors in adult male mice, providing a new target for neuropathic pain treatment.

Applications and technical challenges of MALDI mass spectrometry imaging in microbial ecosystems and metabolic network research - Dongxue Wang; Danni Feng; Yang Yang; Hailong Xie; Lin Liu (Archives of Microbiology, 2026)

Changes in structure, digestion, and curcumin release properties of starch constructed by protein fibrils-OSA starch interactions - Danni Jin; Xiaoyan Wang; Yihui Li; Jinye Long; Zhengyu Huang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2026)

Water-carbon intensity transition driven by the inter-basin water transfer project: spatiotemporal patterns and attribution analysis - Jingru Ji; Jingwen Zhang; Zejun Li; Danni Jia; Tianzi Wang; Kairong Lin; Xiaohong Chen (Journal of Cleaner Production, 2026)

Discrepancies in microbial nitrogen cycling among diverse karst hydrological systems: enhanced nitrate reduction potential in karst conduits - Danni Zhu; Yi Li; Lihua Niu; Changsong Zhou; Lianjie Fan; Haiping Lu; Li Lin (CATENA, 2026)

Modeling the evolution of water-environment-economy coupling system with the impacts of inter-basin water transfer project - Danni Jia; Jingwen Zhang; Zejun Li; Maoyuan Feng; Kairong Lin; Xiaohong Chen; Xiaohui Lei; Lixin He; Chao Ma; Jingru Ji (Journal of Hydrology, 2026)

Salvianolic acid A reduces lipotoxicity injury of cardiomyocytes by orchestrating oxidative stress and inflammation via Akt/Nrf2/NF-κB axis - Lin Li; Siqi Du; Xianghui Meng; Liding Bai; Danni Huang; Fengjie Zhou; Wenwen Li; Xianzhe Qiu; Yulin Qi; Yanyan Wang; Yao Chen; Yuhong Li (Journal of Molecular Histology, 2026)

Mild-condition fractionation of lignocellulose into carbohydrates and water-soluble lignin - Danni Xie; Minsheng Lin; Chang Geun Yoo; Qiang Yang (Biomass and Bioenergy, 2025)

Enhancing separation and anti-fouling performance of cellulose acetate ultrafiltration membranes by introducing natural deep eutectic solvent - Danni Lin; Sisi Hu; Leyuan Zhou; Xiaojuan Ma; Lihui Chen; Dong Wang; Liulian Huang (Journal of Water Process Engineering, 2025)

Switching from flood to drip irrigation changes soil labile organic carbon in arid agricultural fields - Danni Wang; Fangfang Qin; Shiying Lin; Yan Wu; Yongxiang Yu; Yaying Li; Huaiying Yao (Environmental Research, 2025)

Regulating the morphological structure of cellulose acetate ultrafiltration membrane by adjusting the ratio of N, N-dimethylacetamide: N-methyl pyrrolidone in co-solvent to enhance separation and anti-fouling performance - Minfu Mo; Yaling Lin; Danni Lin; Xiaojuan Ma; Yubin Hong; Lihui Chen; Dong Wang; Liulian Huang (Desalination, 2025)

Long-term gap regeneration processes in a primary temperate forest of Northeast China: Evidence from integrated multi-temporal remote sensing and field surveys - Danni Wu; Deliang Lu; Chunyu Zhu; Xiaowen Ge; Litao Lin; Tian Gao; Jiaojun Zhu (Forest Ecology and Management, 2025)

Intestinal barrier disruption by cadmium and microplastics: Mechanistic insights from integrated metabolomic and proteomic analysis in mice - Jiajie Yang; Danni Wang; Junyu Huang; Ting Zhao; Maoting Chen; Shengxuan Lin; Xinqi Yu; Falong Yang; Haifeng Liu; Shiwen Xu; Dechun Chen (Environmental Pollution, 2025)

Dynamic pore engineering in COF-based nanozymes: Construction of hydrogen-bond-mediated confinement catalysis for enhanced asymmetric aldol reactions - Shizhao Wang; Qi Chen; Jiankang Li; Danni Lin; Ka Li; Chuangxin Dong; Xiao Xiao; Fen-Er Chen (Chemical Engineering Journal, 2025)

A novel approach based on PEM electrolysis technology for iron recovery from acid mine drainage: performance and mechanism - Danni Li; Zirui Luo; Qiming Mao; Lin Luo (Environmental Research, 2025)

Pyrolysis of pig waste from intensive farming operations: Kinetics, product distribution, and transformation of endogenous heavy metals - Fengxiao Zhao; Danni Li; Hongyuan Chen; Xianhai Zeng; Lu Lin; Haoran Yuan; Rui Shan; Yong Chen (Journal of Hazardous Materials, 2025)

High-yield bioconversion of glycerol to L-malic acid in Aspergillus niger via systematic engineering of glycerol catabolism and minimal glucose supplementation - Licheng Zhang; Hongzhi Jin; Danni Jiao; Weiqin Lin; Jiao Liu; Hao Liu (Chemical Engineering Journal, 2025)

A ratiometric fluorescent biosensor based on catalytic hairpin assembly reaction for ultrasensitive detection of aflatoxin-producing genes - Tao Yu; Xin Chen; Danni Sun; Dezhao Kong; Zhirong Wang; Feng Lin; Yaqi Li (Food Bioscience, 2024)

The formation of yukonite from FeIII-AsV slurries: Kinetic studies and implications for calcium arsenate treatment - Danni Zhang; Min Li; Ying Wang; Qiuli Xia; Yumeng Wang; Yuting Jin; Junting Tong; Lin Wang; Dake Xu; Fuhui Wang; Yongfeng Jia (Chemical Engineering Journal, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

Mineralization and microbial utilization of poly(lactic acid) microplastic in soil - Yongxiang Yu; Shiying Lin; Binoy Sarkar; Juan Wang; Xinhui Liu; Danni Wang; Tida Ge; Yaying Li; Biao Zhu; Huaiying Yao (Journal of Hazardous Materials, 2024)

Stabilized Hf-doped Ti/Sb-SnO2 electrode for efficient degradation of tetracycline - Danni Li; Xin Guo; Xiang Shao; Anhui Zhou; Lin Zhu; Yuting Zhang; Binbin Li; Yan Du; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Characterization, in vitro digestibility and release properties of starch-linoleic acid-sodium alginate composite film - Huirong Chen; Xiaoyan Wang; Danni Jin; Mingyue Liu; Xiaonian Wu; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Research International, 2023)

Co-pyrolysis of textile dyeing sludge/litchi shell and CaO: Immobilization of heavy metals and the analysis of the mechanism - Danni Li; Rui Shan; Jing Gu; Yuyuan Zhang; Xianhai Zeng; Lu Lin; Haoran Yuan; Yong Chen (Waste Management, 2023)

Spatiotemporal evolution of soil water erosion in Ningxia grassland based on the RUSLE-TLSD model - Xiujuan Zhang; Danni Wang; Kexin Ma; Dong Sun; Falin Yang; Huilong Lin (Environmental Research, 2023)

Paraburkholderia sp. GD17 improves tomato plant growth and resistance to Botrytis cinerea-induced disease - Anqi Gu; Danni Zhao; Huaqiang Liu; Wei Fu; Guangzhe Li; Lin Hao (Plant and Soil, 2023)

The behavior of heavy metal release from sulfide waste rock under microbial action and different environmental factors - Yingbo Dong; Danni Chen; Hai Lin (Environmental Science and Pollution Research, 2022)

Synthesis of nucleobase-neomycin conjugates and evaluation of their DNA binding, cytotoxicities, and antibacterial properties - Siwen Wang; Mandeep Singh; Mingheng Ling; Danni Li; Krege M. Christison; Joan Lin-Cereghino; Geoff P. Lin-Cereghino; Liang Xue (Medicinal Chemistry Research, 2018)

Effect of the impounding process on the overall stability of a high arch dam: a case study of the Xiluodu dam, China - Danni Luo; Peng Lin; Qingbin Li; Dong Zheng; Hongyuan Liu (Arabian Journal of Geosciences, 2015)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

Cross-talk between NMDA and GABAA receptors in cultured neurons of the rat inferior colliculus - DanNi Cong; ZhengQuan Tang; LongZhu Li; YiNa Huang; Jun Wang; Lin Chen (Science China Life Sciences, 2011)